THE STRUGGLE OF UNITED NUSA DUA IN SEIZING TOURISM MARKET IN BUALU CUSTOMARY VILLAGE - Suputra, Ida Bagus Putu Surya (E-Journal of Cultural Studies; Volume 12, Number 3, August 2019DO - 10.24843/cs.2019.v12.i03.p01, 2019)
This study discusses the existence of United Nusa Dua in its efforts to seize the tourism market in Bualu Village, Benoa District, amid accelerating the tourism sector. The rapid of tourism in this area make the crisis for the peoples especially for their identity. Now, these things being a problems when the tourism aspect doesn’t give the contribution for local peoples and for the latest, it raises the movement of United Nusa Dua. The issues appear in this study are (1) Why United Nusa Dua doing the struggle to seize the tourism market? (2) How is the struggling process of Nusa Dua Bersatu in seizing the tourism market? (3) What is the meaning of United Nusa Dua struggle for local communities in Bualu Village?. This study is using a qualitative research, in which the subject of this study discusses the occurrence of hegemony by the authorities (both local authorities and entrepreneurs capital), in its efforts toward reducing the local tradition into modern ideology that already bring with them. The results showed the initial formation of Civil Society Organizations United Nusa Dua as a form of local resistance in an effort to maintain its presence in the midst of the development of the tourism industry in their region. As for the function of the United Nusa Dua is doing resistance to things that are not yet considered for the local community, and unite the indigenous villagers as a form of community resistance in the struggle to seize the tourism. Keywords: struggle, United Nusa Dua, Tourism Market